2023
DOI: 10.1002/admi.202300316
|View full text |Cite
|
Sign up to set email alerts
|

Fast UV‐ and Visible Light Induced Polymer Network Formation Using Carbene Mediated CH‐insertion Based Crosslinking (CHic) Via Nitrophenyl Diazo Esters

Dennis Rusitov,
Florian Deussen,
Jürgen Rühe

Abstract: The synthesis and characterization of highly photosensitive coatings containing a diazo‐based crosslinker that exhibits high photoreactivity in the near‐visible UV and toward sunlight is present. Nitrophenyl diazo ester (nitroPEDAz) moieties are incorporated into polymer chains via free radical polymerization and generate upon irradiation carbenes, which undergo a CH insertion‐based crosslinking (CHic) reaction. The copolymers are deposited onto substrate surfaces through known coating techniques and then act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Despite these advances, the direct patterning of the polymeric HTL in QLEDs has yet to be shown. Carbene cross-linkers are of great interest due to their high activity and wide applications in optoelectronic devices. Previously, we reported that a series of bis-diazo compounds (X1–X5) can effectively cross-link with polymeric poly­[(9,9-dioctylfluorenyl-2,7-diyl)-alt­(4,4′( N -(4-butylphenyl)))] (TFB) by a photothermal synergistic curing process. , However, these bidentate cross-linkers need high doping ratios to guarantee nearly full solvent resistance of the resulted HTL, requiring large doses of UV irradiation and thus without affording patternability.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these advances, the direct patterning of the polymeric HTL in QLEDs has yet to be shown. Carbene cross-linkers are of great interest due to their high activity and wide applications in optoelectronic devices. Previously, we reported that a series of bis-diazo compounds (X1–X5) can effectively cross-link with polymeric poly­[(9,9-dioctylfluorenyl-2,7-diyl)-alt­(4,4′( N -(4-butylphenyl)))] (TFB) by a photothermal synergistic curing process. , However, these bidentate cross-linkers need high doping ratios to guarantee nearly full solvent resistance of the resulted HTL, requiring large doses of UV irradiation and thus without affording patternability.…”
Section: Introductionmentioning
confidence: 99%
“…While metal-catalyzed methods have been extensively studied for C–H functionalization, , metals typically degrade the aging resistance of rubbers. In the field of chemical biology, carbenes, known for linking small molecules to protein targets, show high reactivity with C–H bonds through C–H insertions. Jürgen Rühe’s group has designed a series of diazo compounds (carbene precursors) which produce carbenes upon UV irradiation or heat, enabling polymer surface modification via carbene-mediated C–H insertions. These optimally designed carbene precursors can be used to facilitate enhanced interactions among WR. Moreover, designing dynamic interactions is an effective approach to impart reprocessable properties to cross-linked polymers. Our group anticipates that introducing dynamic interactions will grant reprocessability to recycled WR.…”
Section: Introductionmentioning
confidence: 99%